2000
DOI: 10.1111/j.1749-6632.2000.tb05213.x
|View full text |Cite
|
Sign up to set email alerts
|

Ibogaine: Complex Pharmacokinetics, Concerns for Safety, and Preliminary Efficacy Measures

Abstract: Ibogaine is an indole alkaloid found in the roots of Tabernanthe Iboga (Apocynaceae family), a rain forest shrub that is native to western Africa. Ibogaine is used by indigenous peoples in low doses to combat fatigue, hunger and thirst, and in higher doses as a sacrament in religious rituals. Members of American and European addict self-help groups have claimed that ibogaine promotes long-term drug abstinence from addictive substances, including psychostimulants and opiates. Anecdotal reports attest that a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 15 publications
2
104
1
3
Order By: Relevance
“…We found that ethanol intake was increased significantly after 2 weeks of extinction, compared with preextinction baseline levels: ibogaine reduced the enhanced ethanol intake to baseline levels. Interestingly, human anecdotal reports also suggest a decrease in craving and relapse to addictive drugs after ibogaine intake (Mash et al, 2000). Together, these findings indicate that ibogaine reduces ethanol intake, suggesting that the identification of its molecular mechanism of action for this effect may be beneficial.…”
Section: Ibogaine Attenuates Ethanol Self-administrationmentioning
confidence: 80%
“…We found that ethanol intake was increased significantly after 2 weeks of extinction, compared with preextinction baseline levels: ibogaine reduced the enhanced ethanol intake to baseline levels. Interestingly, human anecdotal reports also suggest a decrease in craving and relapse to addictive drugs after ibogaine intake (Mash et al, 2000). Together, these findings indicate that ibogaine reduces ethanol intake, suggesting that the identification of its molecular mechanism of action for this effect may be beneficial.…”
Section: Ibogaine Attenuates Ethanol Self-administrationmentioning
confidence: 80%
“…Ibogaine is a naturally occurring compound with antiaddictive properties (Mash et al, 2000). A few investigations in vivo have demonstrated that ibogaine is rapidly transformed to 12-hydroxyibogaine (noribogaine), which persists in the bloodstream for at least 1 day (Baumann et al, 2001a;Mash et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that ibogaine facilitates abstinence towards many drugs (morphine, heroin, cocaine, nicotine, alcohol, and psychostimulants) by reducing withdrawal symptoms. [15][16][17] This effect does not seem to be due to its direct interaction with an ibogaine receptor alone, but may well also involve synthesis of the glial cell line-derived neurotrophic factor (GDNF) by dopaminergic neurons. 18,19 Its high lipophilicity (Log P (o/w) 3.6) 20 and rapid, sustained accumulation in the mouse brain 15,21 make ibogaine an attractive candidate as a vector for new g-emitting radiotracers for in vivo imaging of the brains of addicts.…”
Section: Introductionmentioning
confidence: 99%